ANALISIS FASIES BATUAN PERM-TRIAS DAN PROSPEKSI BATUAN INDUK DAN RESERVOIR DI CEKUNGAN TIMOR, NUSA TENGGARA TIMUR - Andi Heri Prastian (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Timor Basin is one of the basin in the Eastern Indonesia wich could has a greatest hydrocarbon potential, however the geological conditions are poorly understood due to the complexity of geological condition, lack of geological and geophysical data, and overwhelming of many different geological concept. This research were conducted in the Kekneno Area, Nenas, South Central Timor, East Nusa Tenggara.The purpose of this study is to arrange a complete sequence of lithostratigraphy, analysis of depositional environment facies, macropaleontological, petrographic and organic petrology analysis. It could compare the relationship between rocks deposited in specific depositional environment with potential as a reservoir and source rock.The method of this study is done by geological field observation by measuring stratigraphic section in some geological traverses to taking the stratigraphy data in detail, and laboratory analysis as petrographic analysis, paleontology, and organic petrology.The result of the facies analysis show that Permian aged rocks deposited on the Middle Fan and Lower to Upper Slope Facies. The Triassic rocks deposited on the Outer Fan, Outer Shelf to Upper Slope, Middle Fan and Inner Fan Facies. From analysis of organic petrology, rock as a potential source rock is black shale of Niof Formation deposited on Outer Fan Facies, with high Vitrinite Maceral composition (87.1%) were included in the Gas Prone Potential category (>95%). Sandstones of Babulu and Cribas Formation from petrographic anaysis indicate poorer levels percentage of porosity is very small (<5%) were included in the classification of bad, so both of the formations are not good potential as a reservoir.